Persiapan Dunia Kerja bagi Siswa SMKN 39 Jakarta: Edukasi Penulisan CV, Psikotes, dan Wawancara - Rahmatika, Rina; Grasiaswaty, Novika; Bagaskara, Sunu (Amalee: Indonesian Journal of Community Research and Engagement, 2021)
Vocational students feel that it is more difficult to compete for jobs after completing their education. In fact, they are expected to find it easier to get a job because they have been equipped with specific skills that are in accordance with their majors. Through the training, it is hoped that it can help vocational students to prepare themselves to compete in the job market. The method used is counseling and providing information to 27 SMKN 39 Jakarta students who will prepare for internships. Based on the statistical analysis of paired samples t-test, there was an increase of 28.89 points between before and after the participants attended the training. This shows that the training provided is effective in preparing participants to meet the job market demands. Siswa SMK merasa bahwa lebih sulit bersaing untuk mendapatkan pekerjaan setelah menyelesaikan pendidikannya. Padahal, lulusan SMK diharapkan lebih mudah mendapatkan pekerjaan dikarenakan sudah dibekali keterampilan khusus yang sesuai dengan jurusannya. Melalui kegiatan pelatihan yang dilakukan ini, diharapkan dapat membantu siswa SMK untuk mempersiapkan diri bersaing di dunia kerja. Metode yang digunakan yaitu dengan penyuluhan dan pemberian informasi pada 27 siswa SMKN 39 Jakarta yang akan bersiap untuk magang. Berdasarkan analisis statistik t-test sampel berpasangan, terdapat peningkatan sebesar 28,89 poin antara sebelum dan setelah peserta mengikuti pelatihan. Hal ini menunjukkan bahwa kegiatan pelatihan yang dilakukan efektif dalam mempersiapkan peserta memasuki dunia kerja.